Socio-economics: Further Steps - Амитаи Этциони (Journal of Economic Sociology, 2010)
In this fragment the author analyzes the current state and dynamics’ development of socio-economics in the context of its interaction and competitiveness with neoclassical theory.  The explanation power of these two paradigms is compared. The questions of infrastructural development of socio-economics are under focus.